O controle verbal do comportamento: um estudo exploratório acerca da legislação sobre pessoas com necessidades especiais - Campos, Ana Carolina Heise Furquim de (2009)
Social groups are responsible for an individual to maintain a determined behaviour through a social reinforcement. When a consequence needs to be reached in the long run, it is important that the group supports the individual behaving through other established contingencies. For situations in which the consequences are too late and don t allow the selection and maintenance of the response, it is necessary to have rules to bridge this gap. Considering law as a rule, its form is a factor to be considered during its analysis. Some rules can describe all the relations of a contingency, the events that occur prior to a response, the actual response and its consequence. The objective of this paper is to analyse the relation between the characteristics of the formulation of the laws relative to the rights of the people with desabilities (if they are or are not formed as a rule) and their impact on the behavior of citizens, through the claims presented to the Grupo de Atuação Especial de Proteção às Pessoas com Deficiência (Pró-PD). The legislation regarding people with desabilities and the claims made to Pró-PD were classified in six topics: Accessibility, Education, Health, Employment, Exemptions and General. The articles on Accessibility and Education were analysed according to their form, being classified as: verbal behaviour of the legislator, rule, specific response, generic response and environment to be created. The results demonstrated that the majority of the articles, more than 80% related to Education and Accessibility, can t be considered a rule, as they don t describe a contingency relationship between two events. The results suggest that, if the laws are stimuli that evoke responses, the articles that are rules are perhaps being fulfilled and there should be a smaller number of claims in relation to them. The articles that are not rules don t evoke responses that should be obtained, and the absence of these responses would evoke the response to claim the rights relating to the topic of the article in a control agency